2012
DOI: 10.3329/bjmm.v6i1.19352
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Acinetobacter species and their antimicrobial resistance pattern in an Intensive Care Unit (ICU) of a tertiary care hospital in Dhaka, Bangladesh

Abstract: Critically ill patients acquire an infection during their stay in an intensive care unit (ICU) and the frequency of these infections varies considerably in different populations and clinical settings. The purpose of this study was to know the antimicrobial sensitivity pattern of Acinetobacter isolates from tracheal aspirate, blood from central venous catheter, peripheral blood, urine and endotracheal tube of patients admitted in ICU at BSMMU(Bangabandhu Sheikh Mujib Medical University) hospital, Dhaka, Bangla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Another study inHFRCMCH in 2013 showed most isolates were from blood followed by respiratory tract 17 . In BSMMU, 50% Acinetobacter species were isolated from blood (central venous catheter and peripheral blood) which was similar to our study 18 . Another study conducted in Karachi showed 44% of organisms were solely from blood 19 .In BIRDEM hospital; Acinetobacter species were isolated from Blood 18.4%, urine 4.7% and respiratory secretion 40.9% 18 .…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Another study inHFRCMCH in 2013 showed most isolates were from blood followed by respiratory tract 17 . In BSMMU, 50% Acinetobacter species were isolated from blood (central venous catheter and peripheral blood) which was similar to our study 18 . Another study conducted in Karachi showed 44% of organisms were solely from blood 19 .In BIRDEM hospital; Acinetobacter species were isolated from Blood 18.4%, urine 4.7% and respiratory secretion 40.9% 18 .…”
Section: Introductionsupporting
confidence: 89%
“…In BSMMU, 50% Acinetobacter species were isolated from blood (central venous catheter and peripheral blood) which was similar to our study 18 . Another study conducted in Karachi showed 44% of organisms were solely from blood 19 .In BIRDEM hospital; Acinetobacter species were isolated from Blood 18.4%, urine 4.7% and respiratory secretion 40.9% 18 . Acinetobacter colonization has been reported from the respiratory tract (41%) followed by urinary tract (25.5%), wound (20%) and blood (12.7%) in a study conducted in India 20 .…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many authors have reported A. lwoffii as a drug susceptible organism as compared to A. baumannii. [36][37][38] All isolates of S. maltophilia were resistant towards ceftazidime, cefepime, imipenem and meropenem. However, it was found that only 26.6% isolates were resistant to piperacillintazobactum and 13.3% towards gentamicin and amikacin.…”
Section: Resultsmentioning
confidence: 99%
“…In Bangladesh, AB was isolated from a third of clinical samples from the intensive care unit (ICU) of a university hospital in 2010, and two-thirds of the isolates were resistant to carbapenems (106). In a seven-center study on Gram-negative bloodstream infections conducted between March 2009 and February 2010 in Sri Lanka, approximately 40% of 71 AB isolates were resistant to the carbapenems (107).…”
Section: South Asiamentioning
confidence: 99%